New considerations in the design of clinical trials for the treatment of acute leukemia - Hourigan, Christopher S (2011)
There is great need for improved therapy for patients with acute leukemia. The current systems of clinical drug development and delivery of leukemia care are imperfectly adapted to the optimal identification and testing of future regimens. Novel clinical trial design with increased enrolment and appropriate end point selection would facilitate more efficient validation of candidate therapies. Clinical outcomes registries and biological sample storage would allow patient and leukemic factor substratification for the development of the next generation of targeted personalized therapy. We believe that the standard of care for patients in the USA diagnosed with acute leukemia, if treated with curative intent, is referral to a specialized center where an appropriate clinical trial can be offered.